The Effect Of Surface Roughness On Tensile Strength Of Fiberglass Reinforced Polymer Composite - Ibrahim, Muhammad Najib (2019)
In composites manufacturing, the surface roughness of the glass fiber reinforced polymer (GFRP) exhibit significant parameter on the mechanical properties of the composite. Thus, in this study, the relationship between the surface roughness and tensile strength due to slip is evaluated. The composite was fabricated by using combination of vacuum compression followed by curing in the autoclave. Set of fiberglass are prepared with different grit size at 400, 600 and 800 at the tab region were tested using tensile test. The parameter is varied by repeating each set of the fiberglass with different frequency of sanding at four (4), eight (8) and twelve (12) times. The effect of the surface roughness using different grit size is analysed using the value tensile strength obtained along with the image produced from optical microscope. At the end of the report, it is expected to obtain optimum surface roughness produced by the grit and the correlation with tensile strength obtained from the tensile testing.